PENGARUH FEE AUDIT, AUDIT TENURE, UKURAN PERUSAHAAN, ROTASI AUDITOR, DAN EFEKTIVITAS KOMITE AUDIT PADA KUALITAS AUDIT - Rista Benu; Pohan, Hotman Tohir (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2025)
This study aims to analyze the influence of audit fees, audit tenure, company size, auditor rotation, and audit committee effectiveness on audit quality. The sample used consisted of 39 companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period from 2017 to 2020. The sampling technique employed was purposive sampling, and the analysis method used was multiple regression analysis. The independent variables in this study consist of audit fees, audit tenure, company size, auditor rotation, and audit committee effectiveness, while the dependent variable is audit quality. The results of this study indicate that only one hypothesis was accepted, which is company size, while the other four hypotheses were rejected. This suggests that the company size variable has a positive influence on audit quality. The results of this study are expected to improve audit quality by optimizing internal controls related to both large and small-sized companies.